2019
DOI: 10.1111/jon.12679
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Damage in Normal Appearing White Matter Contributes to Impaired Cognitive Processing Speed in Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE Cognitive impairment is a core symptom in multiple sclerosis (MS). Damage to normal appearing white matter (NAWM) is likely involved. We sought to determine if greater myelin heterogeneity in NAWM is associated with decreased cognitive performance in MS. METHODS A total of 27 participants with MS and 13 controls matched for age, sex, and education underwent myelin water imaging (MWI) from which the myelin water fraction (MWF) was calculated. Corpus callosum, superior longitudinal fascicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
2
19
2
Order By: Relevance
“…4E could more profoundly exacerbate conduction abnormalities along the length of any particular axon. These changes could, in turn, explain the frequent and disabling nonfocal symptoms affecting MS patients such as fatigue, cognitive impairment, and depression (51) and are consistent with diffusion tensor imaging abnormalities in the white matter of cognitively impaired MS patients (52).…”
Section: Neurosciencementioning
confidence: 58%
“…4E could more profoundly exacerbate conduction abnormalities along the length of any particular axon. These changes could, in turn, explain the frequent and disabling nonfocal symptoms affecting MS patients such as fatigue, cognitive impairment, and depression (51) and are consistent with diffusion tensor imaging abnormalities in the white matter of cognitively impaired MS patients (52).…”
Section: Neurosciencementioning
confidence: 58%
“…Changes in diffusion-based parameters, in particular NODDI and myelin water fraction and magnetization transfer ratio, were observed as well. These changes were correlated with disability, cognitive impairment, and the degree of brain atrophy in multiple sclerosis patients and therefore seem to play an important clinical role in the extent of disease symptoms [ 62 ]. The reported histopathological samples from such regions show axonal pathology and microglial activation depending on the distance to focal MS lesions [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since MHI captures a change in mean and variance, it is more sensitive to myelin damage than using mean MWF alone, particularly in cross-sectional studies with limited sample size. Recently, Abel et al 20 showed that MWF variance was higher in MS and more consistent between healthy individuals than mean MWF. They also found an inverse relationship between myelin heterogeneity and cognitive processing speed performance in MS, which was not significant using the mean MWF.…”
Section: Discussionmentioning
confidence: 99%
“…They also found an inverse relationship between myelin heterogeneity and cognitive processing speed performance in MS, which was not significant using the mean MWF. 20 Furthermore, Wearn et al 21 proposed that T2 heterogeneity in the brain may be a superior measure than mean T2 to predict cognitive decline and to be used as an early marker of Alzheimer’s disease pathology. These past findings support that MHI may be a more sensitive metric to detect subtle alterations in cervical cord myelin that may not be evident with mean MWF measures alone.…”
Section: Discussionmentioning
confidence: 99%